2017
DOI: 10.1016/j.cell.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Environmental and Endogenous Toxins Induces BRCA2 Haploinsufficiency and Genome Instability

Abstract: SummaryMutations truncating a single copy of the tumor suppressor, BRCA2, cause cancer susceptibility. In cells bearing such heterozygous mutations, we find that a cellular metabolite and ubiquitous environmental toxin, formaldehyde, stalls and destabilizes DNA replication forks, engendering structural chromosomal aberrations. Formaldehyde selectively depletes BRCA2 via proteasomal degradation, a mechanism of toxicity that affects very few additional cellular proteins. Heterozygous BRCA2 truncations, by loweri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 59 publications
5
142
1
Order By: Relevance
“…The distinct response to SMARCAL1 depletion in these cell lines may reflect cell-type specific mechanisms by which fork protection could contribute to chemoresistance. In line with this hypothesis, lack of fork protection is accompanied by sensitivity to replication stress-inducing agents in BRCA1/2-deficient B lymphocytes, U2OS cells and ovarian cancer cells (Ding et al, 2016; Dungrawala et al, 2017; Ray Chaudhuri et al, 2016), while it does not result in significant alterations of cell viability in BRCA2-deficient hamster cells, HeLa cells and human breast epithelial cells subjected to replication stress (Schlacher et al, 2011; Tan et al, 2017). Future studies will be required to unravel the pathways by which fork protection may elicit chemoresistance.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The distinct response to SMARCAL1 depletion in these cell lines may reflect cell-type specific mechanisms by which fork protection could contribute to chemoresistance. In line with this hypothesis, lack of fork protection is accompanied by sensitivity to replication stress-inducing agents in BRCA1/2-deficient B lymphocytes, U2OS cells and ovarian cancer cells (Ding et al, 2016; Dungrawala et al, 2017; Ray Chaudhuri et al, 2016), while it does not result in significant alterations of cell viability in BRCA2-deficient hamster cells, HeLa cells and human breast epithelial cells subjected to replication stress (Schlacher et al, 2011; Tan et al, 2017). Future studies will be required to unravel the pathways by which fork protection may elicit chemoresistance.…”
Section: Discussionmentioning
confidence: 60%
“…Recent studies have reported that the mammary epithelial cells of BRCA1 mutation carriers exhibit defective protection of stalled replication forks despite being fully functional for other BRCA1 activities, including DSB repair by HDR and DNA damage checkpoint signaling (Pathania et al, 2014). Extensive replication stress-induced fork degradation was also recently observed in cells carrying BRCA2 heterozygous truncating mutations (Tan et al, 2017). These observations raise the possibility that maintenance of replication fork stability is a key early event in BRCA1/2-mediated tumor suppression.…”
Section: Discussionmentioning
confidence: 78%
“…Exposure of cells to either formaldehyde or acetaldehyde was found to lead to proteasomal degradation of BRCA2 (Tan et al 2017). As a result of reduced protein levels, cells heterozygous for cancer-associated BRCA2 mutations, which normally behave like wild-type cells due to the presence of wild-type BRCA2 from one allele, show evidence of BRCA2 loss of function, including loss of replication fork protection and increased chromosomal aberrations.…”
Section: The Toxic Effects Of Environmental and Metabolic Aldehydementioning
confidence: 99%
“…Moreover, the expression BRCA1 and BRCA2 tumor suppressors genes, known to contribute to DNA repair [130], has been associated to a protective role against endogenous acetaldehyde toxicity [131]. Consequently, endogenous aldehydes may be implicated in triggering carcinogenesis in BRCA2 mutation carriers [132]. …”
Section: Alcohol Toxicity On Stem Cells: In Search For Molecular Mechmentioning
confidence: 99%